2018
DOI: 10.1039/c7nr09049h
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient charge transfer through a double Z-scheme mechanism by a Cu-promoted MoO3/g-C3N4 hybrid nanocomposite with superior electrochemical and photocatalytic performance

Abstract: Herein, a novel Cu-MoO3/g-C3N4 hybrid nanocomposite was successfully synthesized by a two-step strategy of one-pot pyrolysis followed by the impregnation method. The structure, phase, morphology and electronic environment of MoO3, g-C3N4 and Cu in the composite were determined by various characterization methods. The oxygen vacancies of MoO3 were ascertained by UV-DRS, Raman, and XPS analysis. The formation of the heterostructure was characterised by electrochemical measurements. The photocatalytic performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(84 citation statements)
references
References 45 publications
6
73
0
Order By: Relevance
“…However, the high photoinduced charge‐carrier recombination rate and low photon adsorption of only blue light (450 nm) render g‐C 3 N 4 far from the performance level required for practical utilization . It is generally accepted that high photocatalytic activity could be obtained by the construction of heterostructured nanocomposites, and only type II and Z‐scheme heterostructured semiconductor photocatalysts can sufficiently improve the fast spatial separation of photoinduced electron–hole pairs, prolong their lifetime and promoting the photocatalytic activity . Furthermore, the construction of 2D–2D layered heterostructures has drawn increasing attention because it can improve the interfacial contact and possesses some unique properties that are of benefit to photocatalysis.…”
Section: Introductionmentioning
confidence: 59%
“…However, the high photoinduced charge‐carrier recombination rate and low photon adsorption of only blue light (450 nm) render g‐C 3 N 4 far from the performance level required for practical utilization . It is generally accepted that high photocatalytic activity could be obtained by the construction of heterostructured nanocomposites, and only type II and Z‐scheme heterostructured semiconductor photocatalysts can sufficiently improve the fast spatial separation of photoinduced electron–hole pairs, prolong their lifetime and promoting the photocatalytic activity . Furthermore, the construction of 2D–2D layered heterostructures has drawn increasing attention because it can improve the interfacial contact and possesses some unique properties that are of benefit to photocatalysis.…”
Section: Introductionmentioning
confidence: 59%
“…Many research groups have reported their findings in designing unidirectional double Z‐scheme‐based photocatalysts for water redox reactions and degradation of harmful pollutants . Moreover, our group has reported photocatalytic reduction of Cr 6+ → Cr 3+ and water → H 2 over Cu–MoO 3 /g‐C 3 N 4 hybrid nanocomposite . Ternary Ag 2 CO 3 /CeO 2 /AgBr photocatalyst has been reported by Wen et al with double Z‐scheme configuration performing photodegradation of levofloxacin .…”
Section: Introductionmentioning
confidence: 61%
“…Understandably then, scientists started focusing on the construction of ternary semiconductors with dual Z‐scheme pathway for more effective charge separation. Many research groups have reported their findings in designing unidirectional double Z‐scheme‐based photocatalysts for water redox reactions and degradation of harmful pollutants . Moreover, our group has reported photocatalytic reduction of Cr 6+ → Cr 3+ and water → H 2 over Cu–MoO 3 /g‐C 3 N 4 hybrid nanocomposite .…”
Section: Introductionmentioning
confidence: 84%
“…24 All the catalysts exhibited analogous PL spectra, whereas weak peaks for NFO were observed in the range of 380 nm to 500 nm, which might be ascribed to the surface oxygen vacancies and defects of NFO originating from excitonic PL. 31 Aer the addition of NFO species, an obvious decrease in the intensity of the PL spectra for P-CN was observed, suggesting that NFO modi-cation efficiently prevented electron-hole pair reunion. Finally from these characterizations, well-supporting results in favor of photoinduced charge migration and separation were obtained for 20 wt% NFO@P-CN.…”
Section: Conrmation Of the Photogenerated Electron-hole Separation Fmentioning
confidence: 97%